2020
DOI: 10.1136/openhrt-2019-001134
|View full text |Cite
|
Sign up to set email alerts
|

Management of patients with acute ST-segment elevation myocardial infarction in Russian hospitals adheres to international guidelines

Abstract: ObjectiveRussia has one of the highest cardiovascular mortality rates. Modernisation of the Russian health system has been accompanied by a substantial increase in uptake of percutaneous coronary intervention (PCI), which substantially reduces the risk of mortality in patients with acute ST-elevation myocardial infarction (STEMI). This paper aims to describe contemporary Hospital treatment of acute STEMI among patients in a range of hospitals in the Russian Federation.MethodsThis study used data from a prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
(20 reference statements)
0
9
0
1
Order By: Relevance
“…One of the key factors that may contribute to CVD mortality differences is the effective treatment and medical prevention of CVD. There is evidence for example, that since 2010 there has been a reduction of in hospital mortality from myocardial infarction, most likely related to a very rapid expansion of percutaneous coronary intervention facilities across Russia 7 , 37 . Moreover, more effective and longer term control of blood pressure in the Norwegian population, and the irregular control of it in Russia 38 may also be a relevant factor that is not reflected in the mean blood pressures per se.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the key factors that may contribute to CVD mortality differences is the effective treatment and medical prevention of CVD. There is evidence for example, that since 2010 there has been a reduction of in hospital mortality from myocardial infarction, most likely related to a very rapid expansion of percutaneous coronary intervention facilities across Russia 7 , 37 . Moreover, more effective and longer term control of blood pressure in the Norwegian population, and the irregular control of it in Russia 38 may also be a relevant factor that is not reflected in the mean blood pressures per se.…”
Section: Discussionmentioning
confidence: 99%
“…Several attempts have been made to explain the elevated mortality rate in Russia including socioeconomic level, standard of medical care, and lifestyle factors 4 7 . It is acknowledged that behaviours such as smoking 8 , 9 and alcohol intake 10 12 and contextual factors such as gross domestic product (GDP) per capita 13 are likely to contribute the elevated mortality rate in Russia.…”
Section: Introductionmentioning
confidence: 99%
“…Despite advances in treatment, patients with acute myocardial infarction (MI) have a poor long-term prognosis. Hospitalized patients with ST-segment elevation MI (STEMI) have an increased mortality rate [ 2 , 3 ], and mitral regurgitation (MR) is a common complication of STEMI [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Early primary percutaneous coronary intervention (PPCI) has now been set up as the rst-line treatment for subjects who has acute myocardial infarction (MI) [1] . A randomized trial of moderate size [2][3][4][5][6][7] showed there is a signi cant increase in major adverse cardio-cerebral events (MACCE) after undergoing the PPCI.…”
Section: Introductionmentioning
confidence: 99%
“…Early primary percutaneous coronary intervention (PPCI) has now been set up as the rst-line treatment for subjects who has acute myocardial infarction (MI) [1] . A randomized trial of moderate size [2][3][4][5][6][7] showed there is a signi cant increase in major adverse cardio-cerebral events (MACCE) after undergoing the PPCI. Indeed, in high-risk patients and lesion subsets, including those older than 65 years old, with renal dysfunction, diabetes mellitus (DM), thrombotic target lesion and multi-vessel disease residual atherothrombotic risk remains substantial.…”
Section: Introductionmentioning
confidence: 99%